Dynamic Computational Theory Construction and Simulation for the Dynamic Relationship Between Challenge Stressors and Organizational Citizenship Behaviors - Chen, Long; Zhang, Li; Bu, Qiong (Frontiers in Psychology, 2022)
This study explores the dynamic feature of organizational citizenship behavior under the condition of challenge stressor, as this has not been addressed by previous research. Combining the cybernetic theory of stress and social exchange theory, this study builds a dynamic computational model regarding the circular causality between challenge stressor and organizational citizenship behavior. By conducting a series of simulation experiments, we validate and demonstrate important questions regarding organizational citizenship behavior. Specifically, when both the initial value of challenge stressor and the importance of challenge appraisal are higher, organizational citizenship behavior tends to show a sharped inverted U shape (i.e., organizational citizenship behavior increases and decreases rapidly) at the early stage. When both the equilibrium level of job satisfaction and the initial value of challenge stressor are higher, organizational citizenship behavior will show an inverted N shape over time. The number and frequency of assigned challenge tasks have an interactive effect on the accumulation of organizational citizenship behavior within a period. Our theory contributes to identifying the dynamic relationship between challenge stressor and organizational citizenship behavior. Findings from dynamic computational theory can offer suggestions for managers to encourage employees’ engagement in organizational citizenship behavior.